Survey and study on yield and quality of patchouli oil in Aceh Barat Daya District, Indonesia based on original area of raw materials, methods and length of distilation - N. Arpi; Cut Erika; Dewi Ermaya (Syiah Kuala University, 2011)
Patchouli oil from patchouli plant (Pogostemon cablin Benth) is one of important essential oils as a source of Indonesian foreign exchange. It is about 90% of world patchouli oil from Indonesia (Suara Merdeka, 2006). The objectives of this research were to assess the yield and quality of patchouli oils from four different villages in the sub district of Kuala Batee, Aceh Barat Daya based on the original area of raw material and the method of distillation, also based on length of distillation. The nested design was used in this research with the treatment of two factors combination, with the level of one factor similar but not identical. The treatments were the original area of raw material and the distillation method used in the original area of the raw material (BM1-4), and the length of distillation (5, 6, and 7 hours). Parameter observed were yield, specific gravity, refractive index, alcohol solubility, the concentration of patchouli alcohol, ester number, acid number, and the sensory test on color and clarity. The results indicated that the original area of raw material and distillation method (BM) had a significant effect on yield, refractive index, clarity, and acid number. The yield was 2.85%-4.5%, and patchouli oil from BM4 and BM2 gave higher yield but lower patchouli alcohol concentration, and clarity. The results also indicated that the longer time of distillation the higher patchouli oil yield, specific gravity, and patchouli alcohol concentration. However, it affected the lower alcohol solubility and clarity, the higher ester number, and the darker color of the patchouli oil. The concentration of patchouli alcohol in this study ranges from 21.36% to 34.03%. Patchouli oil yielded in this research have complied the SNI 06-2385-2006